2011
DOI: 10.1111/j.1365-2753.2011.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Collective learning, change and improvement in health care: trialling a facilitated learning initiative with general practice teams

Abstract: This trial of the learning practice programme shows that, with facilitation and the appropriate input of resources, general practice teams can successfully apply learning organization principles to produce quality improvement outcomes. The study also demonstrates the value of action research in researching iterative change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This research also found that sites with external facilitation were appreciative of the time and expertise provided by the facilitators. This finding supports that of Bunniss et al [ 17 ] that the value of the external facilitators became apparent to the participant after the first facilitation session, and their contributions were recognized by teams as valuable.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This research also found that sites with external facilitation were appreciative of the time and expertise provided by the facilitators. This finding supports that of Bunniss et al [ 17 ] that the value of the external facilitators became apparent to the participant after the first facilitation session, and their contributions were recognized by teams as valuable.…”
Section: Discussionsupporting
confidence: 91%
“…To improve the quality of acute stroke services [ 11 ] in the Veterans Health Administration (VHA), the VA stroke Quality Enhancement Research Initiative (QUERI) [ 12 ] partnered with VA Center for Applied Systems Engineering (VA-CASE) [ 13 ], an interdisciplinary Veterans Engineering Resource Center (VERC) to provide industrial/systems engineering facilitation and tools to evaluate a stroke learning collaborative [ 14 - 16 ] intervention. Given the complexity of the acute stroke clinical practice changes and the training literature [ 16 ], the collaborative program training [ 17 ] alone is insufficient to produce and sustain practice changes [ 18 ]. Therefore, telephone facilitation is an important and efficient approach to provide facilitation service [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that working towards shared goals can break down barriers between professional groups and enhance communication within practice teams. 20,21 The study presented here suggests, however, that pre-existing effective communication has helped to embed this new approach to collecting patient feedback within general practices.…”
Section: Comparison With Existing Literaturementioning
confidence: 90%
“…One research study showed that applying learning theory to clinical practice teams using facilitated sessions led to successful outcomes for change management. 30 These facilitated activities set the stage for valuable discussion, exchange of experiences, insights, and inquiry surrounding both individual and group ideas for the transition that needs to occur to realize a new care delivery vision.…”
Section: Qsen Competenciesmentioning
confidence: 99%